Healthy and environmentally sustainable food choices: Consumer responses to point-of-purchase actions. (June 2017) - Hoek, A.C.; Pearson, D.; James, S.W.; Lawrence, M.A.; Friel, S.
Highlights: In 3 choice experiments we evaluate actions to promote healthy and sustainable foods. Overall price changes had more effect than health and/or environment logos and labels. Most shifts occurred with close product alternatives (white and brown rice). There was less change with less similar product alternatives (e.g. beef to kangaroo). Consumer responsiveness was mainly influenced by product familiarity and liking. Abstract: There are numerous government and industry actions that could advance consumer choices for healthier and environmentally sustainable food products. This study investigates the effect of point-of-purchase actions; price changes, health and/or environment logos, health and/or environment product information labels. Three hypothetical choice experiments investigated choices between specific products and their healthy and sustainable alternatives: rice (white versus brown rice, n = 280), meat (beef versus kangaroo steak, n = 344) and tomatoes (tinned versus fresh tomatoes for a tomato sauce, n = 320). Data was collected via an online survey from a representative nationwide sample of Australian household grocery buyers (N = 944). Results show that the effects of the investigated actions are very product and consumer segment dependent. In general, price changes, particularly a decreased price (subsidy) for the healthy and sustainable alternatives, had a bigger effect on shifting choices than did a logo and/or label. Product similarity seems to play an important role as we observed the greatest shift in choices in the rice experiment with more respondents opting for brown rice instead of white rice. The responsiveness of consumers to the investigated measures was largely influenced by whether they were familiar with, and liked, the healthy and sustainable product alternative. In conclusion this study indicates that point-of-purchase actions may partially contribute to advance uptake of healthy and sustainable food alternatives. The effects of such measures are expected to be greater when these alternatives are more similar to the standard products for their sensory properties, convenience, product liking and familiarity.